Prevalence and mortality risk of low skeletal muscle mass in critically ill patients: an updated systematic review and meta-analysis - Yang, Hui; Wan, Xi-Xi; Ma, Hui; Li, Zhen; Weng, Li; Xia, Ying; Zhang, Xiao-Ming (Frontiers in Nutrition, 2023)
Background: Patients with critical illness often develop low skeletal muscle mass (LSMM) for multiple reasons. Numerous studies have explored the association between LSMM and mortality. The prevalence of LSMM and its association with mortality are unclear. This systematic review and meta-analysis was performed to examine the prevalence and mortality risk of LSMM among critically ill patients. Methods: Three internet databases (Embase, PubMed, and Web of Science) were searched by two independent investigators to identify relevant studies. A random-effects model was used to pool the prevalence of LSMM and its association with mortality. The GRADE assessment tool was used to assess the overall quality of evidence. Results: In total, 1582 records were initially identified in our search, and 38 studies involving 6891 patients were included in the final quantitative analysis. The pooled prevalence of LSMM was 51.0% (95% confidence interval [CI], 44.5%–57.5%). The subgroup analysis showed that the prevalence of LSMM in patients with and without mechanical ventilation was 53.4% (95% CI, 43.2%–63.6%) and 48.9% (95% CI, 39.7%–58.1%), respectively (P-value for difference = 0.44). The pooled results showed that critically ill patients with LSMM had a higher risk of mortality than those without LSMM, with a pooled odds ratio of 2.35 (95% CI, 1.91–2.89). The subgroup analysis based on the muscle mass assessment tool showed that critically ill patients with LSMM had a higher risk of mortality than those with normal skeletal muscle mass regardless of the different assessment tools used. In addition, the association between LSMM and mortality was statistically significant, independent of the different types of mortality. Conclusion: Our study revealed that critically ill patients had a high prevalence of LSMM and that critically ill patients with LSMM had a higher risk of mortality than those without LSMM. However, large-scale and high-quality prospective cohort studies, especially those based on muscle ultrasound, are required to validate these findings.